HEALING OF DIABETIC FOOT ULCERS IN A TYPE 2 DIABETES MELLITUS PATIENT WITH MONITORING OF BLOOD GLUCOSE LEVELS AT TOARI PUBLIC HEALTH CENTER : A CASE REPORT - JALAL, ANDI RIDWAN; HERMAN, ANDI (Journal Medical Universitas muhammadiyah Makassar, 2025)
This case study presents the management of a diabetic foot ulcer in a 65-year-old female patient with Type 2 Diabetes Mellitus (T2DM) and a history of poor glycemic control. The patient developed an ulcer on the sole of her right foot in June 2020, with an initial random blood glucose level of 358 mg/dL. Due to delayed and inconsistent treatment, the wound progressively worsened. Comprehensive wound care was initiated at the Toari Health Center, employing modern dressing techniques and the moist wound healing approach. The treatment protocol included daily debridement (both autolytic and mechanical), infection control using antiseptics and topical antimicrobials (e.g., iodine), moisture balance maintenance, nutritional support with a high-protein diet, and strict glycemic regulation with oral hypoglycemic agents (Metformin and Glibenclamide). A protective skin barrier was also applied to prevent maceration of the surrounding tissue. After two months of consistent monitoring and treatment, significant wound healing was observed, accompanied by improved glycemic control. This case highlights the importance of integrated wound care and blood glucose management in the successful treatment of diabetic foot ulcers.